Quality of Life Study in Chronic Diseases: More Needed Than Ever - Laurentius Aswin Pramono (Acta Medica Indonesiana)
Numerous thyroid diseases can impact patients’ lives, one of which is Graves’ ophthalmopathy (GO). Graves’ ophthalmopathy is a progressive thyroid-related disease that causes eye symptoms due to an autoimmune reaction targeting thyrotropin/thyroid stimulating hormone (TSH) receptors in the orbital space. This condition can be easily recognized by the patient, including exophthalmos, pain, swelling, double vision, and impaired vision. Globally, the estimated incidence of GO is 3.3–8 per 100,000 in women and 0.9–1.6 per 100,000 in men with the peak incidence between 30-60 years old. The prevalence of GO is 9 per 100,000, with the prevalence of GO among patients with Graves’ disease reaching 30%.